A self-regulated learning enhancement program and mathematics achievement of grade VI students - Sacapaño, Angelita A. (2006)
The study checked the effectiveness of the researcher-made Mathematics Self-Regulated Learning Enhancement Program (MSRLEP) on the mathematics achievement of Grade VI pupils. It was quasi-experimental in nature. The participants came from two intact classes in Roosevelt College-Cainta. The researcher facilitated the 12-hour long sessions using a variety of instructional methods such as lecture, discussion, storytelling, demonstration, puppetry, games, and interviews throughout the training program. The research supports the self-regulated learning theory which states that when students are given opportunities to acquire and develop learning strategies, self-regulation is likely to happen, thus academic achievement is positively affected.
Thesis (Ph.D. Education : Educational Psychology)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching (Elementary) -- Philippines -- Cainta (Rizal).; Self-culture -- Philippines -- Cainta (Rizal); Academic achievement -- Philippines -- Cainta (Rizal); Learning strategies -- Philippines -- Cainta (Rizal)